Intrahepatic fat, abdominal adipose tissues, and metabolic state: magnetic resonance imaging study. Issue 5 (14th March 2017) - Yaskolka Meir, Anat; Tene, Lilac; Cohen, Noa; Shelef, Ilan; Schwarzfuchs, Dan; Gepner, Yftach; Zelicha, Hila; Rein, Michal; Bril, Nitzan; Serfaty, Dana; Kenigsbuch, Shira; Chassidim, Yoash; et al.
Abstract: Background: Intrahepatic fat (IHF) is best known to associate with waist circumference (WC) and visceral adipose tissue (VAT), but its relation to abdominal subcutaneous adipose tissue is controversial. While IHF ≥ 5% dichotomously defines fatty liver, %IHF is rarely considered as a continuous variable that includes the normal range. In this study, we aimed to evaluate %IHF association with abdominal fat subdepots, pancreatic, and renal‐sinus fats. Methods: We evaluated %IHF, abdominal fat subdepots, %pancreatic, and renal‐sinus fats, among individuals with moderate abdominal obesity, using 3‐Tesla magnetic resonance imaging. Results: Among 275 participants, %IHF widely ranged (0.01%‐50.4%) and was lower in women (1.6%) than men (7.3%; P < .001). In an age, sex, and WC‐adjusted models, VAT area ( P < .006) was directly associated with %IHF, while superficial–subcutaneous adipose tissue proportion was inversely associated with %IHF ( P < .006). In these models, renal‐sinus fat was positively associated with %IHF ( P = .005). In an age, sex, WC, and VAT‐adjusted models, elevated liver enzymes, glycemic, lipid, and inflammatory biomarkers were associated with increased %IHF ( P < .003 for all). In these models, the associations remained robust even within the normal range strata of IHF < 5% for triglycerides and chemerin ( P ≤ .004 for all). For the diagnosis of fatty liver, the joint area under the curve of WC, alanine‐aminotransferase, triglycerides/high‐density lipoprotein cholesterol, and homeostasis model assessment of insulin resistance was 0.84(95% CI, 0.79‐0.89). Conclusions: Intrahepatic fat is differentially associated with abdominal fat subdepots. Intrahepatic‐fat as a continuous variable could be predicted by specific traditional parameters, even within the current normal range, and partially independent of VAT.